Surgical Complexity and Intraoperative Obstacles in Mastoidectomy: A Retrospective Study at JRRMCH, Sylhet - Islam, Md Mofakkarul; Rahman, Md Arafat; Mahdi, Syed Mohammod (Journal of Rangpur Medical College, 2025)
Background: Mastoidectomy is a complex otologic procedure with difficult anatomical navigation through the temporal bone. Despite technological advancements, intraoperative difficulties are frequent and may significantly affect surgical outcomes. It is important to understand the predictors and types of intraoperative problems for surgical planning and optimization of patient safety, particularly in low-resource settings. Objective: This study aimed to examine the relationship between surgical complexity, intraoperative complications, and patient or procedural variables in mastoidectomy, providing evidence for surgical planning and risk stratification. Methods: This is a retrospective observational study conducted in Jalalabad Ragib-Rabeya Medical College Hospital (JRRMCH), Sylhet, on 100 mastoidectomy cases operated upon from January 2022 to December 2024. Patient demographics, surgical indications, comorbidity, mastoidectomy type, intraoperative complications, and postoperative outcomes were analyzed. Surgical complexity was graded based on intraoperative findings. Data analysis was performed using SPSS version 27, and significance was considered at p<0.05. Results: Intraoperative challenges were faced by 40% of patients. While age, sex, and comorbidities were not significantly related to the occurrence of challenges (p>0.05), surgical technique was. CWD procedures were more strongly linked to challenges (50%) compared to cortical mastoidectomy (30%) (p=0.002). Bleeding (50%), poor anatomical visualization (62.5%), facial nerve dehiscence (25%), and dura exposure (20%) were the intraoperative challenges, all of which were statistically significant (p<0.001). Cortical mastoidectomy, however, was more frequently associated with uncomplicated procedures. Conclusion: Mastoidectomy type significantly affected intraoperative complexity, with CWD procedures posing more risk for complications. Preoperative identification of high-risk cases and tailored surgical planning are required to minimize intraoperative challenges and optimize outcomes. These findings underscore the need for improved risk stratification and operative preparedness, especially in settings with limited surgical resources. J Rang Med Col. 2025 Sep;10(2): 60-65